The Missing 'Allen–Persons' Cases of Conscience. Issue 1 (May 2014) - Holmes, Peter
Abstract : Cardinal William Allen, Robert Persons, S. J. and the Rev. Gregory Martin supervised the production in about 1581 of a discussion of cases of consciences, which were intended for the use by students trained for the English mission at the Venerable English College, Rome. The principal manuscript copy of these cases previously known is missing a final section. This has now turned up in the Library of the Society of Antiquaries of London. This article consists of an introduction to the manuscript sources, the cases and their doctrine; a transcript of the Latin text; and a translation of it into English.